A Contextual Model for Understanding Intercultural Communication (KULT_online, 2010)
Neuliep's Intercultural Communication: A Contextual Approach is designed for teachers and students who are dealing with intercultural communication (ICC). In addition to providing comprehensive conceptual issues, the work pioneers a contextual model for the study of intercultural communication. It aims at introducing fundamental topics, theories, concepts, and themes that are at the center of ICC. The model is based on the fact that when people from different cultures/co-cultures encounter and exchange verbal and/or non-verbal messages, they do so within a variety of contexts. These include cultural, microcultural, environmental, socio-relational, and perceptual contexts. This edition is unique from its earlier editions for its inclusion of a new chapter on intercultural conflicts and the addition of discussion questions in every chapter.